Vivos no campo de esquecimento: lepra e isolamento compulsório no Espírito Santo (1920-1962) - Araujo, Tania Maria de (2020)
The study aims to analyze the policy of compulsory isolation of people with leprosy in Espírito Santo between the 1920s and 1960s, as well as the perception about the disease and isolation for patients who must have undergone hospitalization. It is an exp